2006
DOI: 10.1002/ejsp.351
|View full text |Cite
|
Sign up to set email alerts
|

Striving for personal power as a basis for social power dynamics

Abstract: It has often been proposed that people are intrinsically motivated to gain or increase power over others. We argue that theoretical underpinnings of such a claim are lacking. Moreover, empirical support for this claim is more convincingly explained by strivings to increase one's sense of agency (personal power) by decreasing dependence on others, rather than by strivings to increase power over others (social power). In two experiments, we directly tested the explanatory value of the personal power concept. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 46 publications
3
90
1
1
Order By: Relevance
“…Power enhances personal control and resources , Van Dijke & Poppe 2006, which motivates some people to seek power and to avoid relinquishing it once they have gained it (Ratcliff & Vescio 2013). Together, this work shows that maintaining power is important for power holders, who monitor their relative power and respond to threats with harsh power assertion.…”
Section: Exercising and Maintaining Powermentioning
confidence: 78%
See 1 more Smart Citation
“…Power enhances personal control and resources , Van Dijke & Poppe 2006, which motivates some people to seek power and to avoid relinquishing it once they have gained it (Ratcliff & Vescio 2013). Together, this work shows that maintaining power is important for power holders, who monitor their relative power and respond to threats with harsh power assertion.…”
Section: Exercising and Maintaining Powermentioning
confidence: 78%
“…Van Dijke & Poppe (2006) and Lammers et al (2016) found that people seek power mainly to increase control over their own lives. This increased sense of control plays a causal role in power holders' optimism and action orientation ).…”
Section: Power and Cognitionmentioning
confidence: 99%
“…Interestingly, the finding that follower control perceptions did not explain endorsement of prototypical leaders points to a drawback of prototypical leadership: Perceiving more control in leaders' decisions suggests that such leaders are, in fact, viewed as having less "hard" power over their followers (van Dijke & Poppe, 2006). Because low identifiers care relatively little about the group and its leader but do perceive prototypical leaders as having less power, prototypical leaders may not have an easy job influencing weakly identified followers.…”
Section: Implications For Leadership Researchmentioning
confidence: 99%
“…In general, power is linked to broad strivings for agency (van Dijke & Poppe, 2006;Overbeck & Park, 2001). Smith, Jostmann, Galinksy, and van Dijk (2008) showed that low power impaired performance on some executive function measures, notably the Stroop task.…”
Section: Power Promotes Self-regulation Of Effortmentioning
confidence: 99%